Cyclic response of a stiffened suction caisson anchor in calcareous silt. (1st April 2020) - Koh, Kai Xiang; Kim, Youngho; Hossain, Muhammad Shazzad
Abstract: The offshore industry attempts to extend the application of suction caisson anchors in calcareous seabed sediments. However, very little data exists on the performance of caisson in calcareous soils. The aim of this paper is to provide insight into the behaviour of a stiffened caisson anchor under cyclic operational loading in lightly overconsolidated calcareous silt. A series of model tests were carried out in a beam centrifuge, varying the mudline load inclination at 0°, 20°, 40°. In each cyclic loading test, three episodes of loading were applied, varying mean load (average load in proportion to the corresponding monotonic capacity) as 30%, 50% and 70%, while the amplitude (defined as the maximum variation from the average load) and number of cycles for each episode were kept constant at 20% and 50 cycles, respectively, and then loaded monotonically. The accumulated displacement and negative excess pore pressure at the trailing side of the skirt tip increased, particularly from the second episode of cyclic loading, with decreasing mudline load inclination angle. The ratio of post-cyclic monotonic capacity to pure monotonic capacity reduced as 1.20, 1.01, and 0.90, with changes of excess pore pressure and effective stress dominating the behaviour for high load inclination angle and cyclic degradation for low load inclination angle. Comparing the results to the performance of other foundations and anchors, it was found that post-cyclic monotonic capacity depends heavily on the embedment depth of the object along with load/mooring inclination, cyclic load amplitude, and seabed material. Highlights: Quantify the performance of a stiffened caisson under cyclic inclined loading in calcareous silt. Different cyclic loading characteristics: (a) mean load; (b) amplitude; (c) number of cycles. Effect of inclined pullout angles on the cyclic performance of a caisson. Comparison studies with various offshore foundations (e.g. DIA, plate anchor, and spudcan foundation).